Load balancing multicast routing based on network coding in wireless mesh network - Xiao-jian SHEN; Zhi-gang CHEN; Li LIU (Tongxin xuebao)
A new load balancing routing measure CRM-LB based on network coding was presented，the CRM-LB increased the considerations of traffic concentration level congestion level all nodes on the path p based on CRM.Wireless mesh network multicast routing CLR based on the CRM-LB was put forward.The protocol can increase network coding opportunities considering the load balancing in network.The performance analysis and simulation results show that the protocol，under the premise of improving multicast throughput，not only to support network coding better，and achieve load balancing in network.